2020
DOI: 10.1103/physrevb.101.184202
|View full text |Cite
|
Sign up to set email alerts
|

Electronic, dielectric, and optical properties of two-dimensional and bulk ice: A multiscale simulation study

Abstract: The intercalated water into nanopores exhibits anomalous properties such as an ultralow dielectric constant. Multiscale modeling and simulations are used to investigate the dielectric properties of various crystalline two-dimensional ices and bulk ices. Although the structural properties of two-dimensional (2D) ices have been extensively studied, much less is known about their electronic and optical properties. First, by using density functional theory and density functional perturbation theory (DFPT), we calc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 44 publications
2
18
0
Order By: Relevance
“…Recently, the out-of-plane dielectric constant ( ε ⊥ ) of nanoconfined water between two graphene sheets and hexagonal boron nitride was measured using atomic force microscopy. In our previous papers, , using both atomistic simulation and continuum model, we found that ε ⊥ is reduced to 2.1 for confined water in channels with height h ≤ 15 Å. This is due to the reduction of degree of freedom as well as liquid to solid phase transition.…”
Section: Introductionmentioning
confidence: 85%
“…Recently, the out-of-plane dielectric constant ( ε ⊥ ) of nanoconfined water between two graphene sheets and hexagonal boron nitride was measured using atomic force microscopy. In our previous papers, , using both atomistic simulation and continuum model, we found that ε ⊥ is reduced to 2.1 for confined water in channels with height h ≤ 15 Å. This is due to the reduction of degree of freedom as well as liquid to solid phase transition.…”
Section: Introductionmentioning
confidence: 85%
“…A queous solutions under nanoscale confinement have attracted considerable interest over the past few years, owing to their unusual structural, dynamical, and physicochemical properties (different from those of their bulk counterparts), as well as to their broad significance for nanoscale chemical, biological, and physical systems such as ion channels/ batteries and water desalination [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] . For instance, numerous experiments and molecular dynamics (MD) simulations revealed that nanoconfined water may freeze into various one-dimensional (1D) and two-dimensional (2D) polymorphous and polyamorphous structures at low temperatures 4,8,10,[16][17][18][19][20][21][22][23][24][25][26][27][28][29] . Fast mass transport and high proton conductivity were also observed for water confined inside nanotubes 2,7,30 .…”
mentioning
confidence: 99%
“…Our results provide mechanistic insights into the behavior of water within a highly nanoconfined pore. This is of direct relevance to the ongoing interest in nanoconfined water as studied either experimentally ( e.g ., refs and ) or computationally ( e.g ., refs and ).…”
mentioning
confidence: 99%